2022
DOI: 10.2478/cpp-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Transcranial Direct Current Stimulation (tDCS) in Anorexia Nervosa Treatment- Case Report

Abstract: Introduction: Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation with considerable potential as a treatment for many CNS disorders. Individuals suffering from eating disorders have elevated rates of lifetime depression, anxiety and obsessive-compulsive disorder, also affecting specific brain regions. More studies assess the effect of brain modulation in anorexia nervosa (AN). This study aimed to evaluate the effect, tolerability and safety of tDCS stimulation in the patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…A low-intensity direct current is used -up to 2000uA-2mA. Possible results confirming the effectiveness of this therapy could be an argument for introducing it to treatment in psychiatric wards or at home [35] Medium and large between-group differences in mood and quality of life and small between-group differences in BMI in the rTMS groups; faster rate of weight gain in the rTMS group compared with the control group at 18 months (BMI over 18.5 kg/m2: 46% vs. 9%). Electroconvulsive Therapy (ECT)…”
Section: Tdcs In Anorexia Nervosamentioning
confidence: 99%
“…A low-intensity direct current is used -up to 2000uA-2mA. Possible results confirming the effectiveness of this therapy could be an argument for introducing it to treatment in psychiatric wards or at home [35] Medium and large between-group differences in mood and quality of life and small between-group differences in BMI in the rTMS groups; faster rate of weight gain in the rTMS group compared with the control group at 18 months (BMI over 18.5 kg/m2: 46% vs. 9%). Electroconvulsive Therapy (ECT)…”
Section: Tdcs In Anorexia Nervosamentioning
confidence: 99%
“…Rzad et al [71] presented a case report involving the application of tDCS on an 18-year-old female participant. The study aimed to assess several aspects, including anthropometric measures, biological factors, and psychological aspects.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…All the studies included in this research employed anodal stimulation on the left dorsolateral prefrontal cortex (DLPFC). Four of the studies [68][69][70][71] followed the international 10-20 system to position the electrodes accurately. This method involves measuring the participant's head to identify specific regions of interest, and based on this, the anodal electrode was placed at F3.…”
Section: Technical Aspects Of Tdcs In An and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results did not show major improvements in AN psychopathology or weight recovery compared with sham tDCS, active tDCS reduced the need for excessive control over food intake and improved body image. In addition, three small open-label studies [ 16 , 45 , 71 ] and one case report [ 67 ] have examined tDCS efficacy of left DLPFC anodal stimulation in people with AN. Although these studies have varied in terms of treatment protocols (e.g., treatment administered three times a week over 6 weeks or once and twice per day over ten days), all studies suggested benefits for core eating disorder symptoms with the pilot studies showing maintained benefits at 1 month follow up post end acute treatment.…”
Section: Introductionmentioning
confidence: 99%